A PROSPECTIVE CLINICAL AND IMMUNOLOGICAL STUDY OF LATE ONSET MYASTHENIA GRAVIS. Issue 11 (14th October 2015) - Sadalage, Girija; Jacob, Saiju; Buckley, Camilla; Hilton-Jones, David; Vincent, Angela; Maddison, Paul
Abstract : There is an increasing incidence and prevalence of MG in older patients (>50 years) – defined as Late Onset Myasthenia Gravis (LOMG). This study aims to define the demographics, clinical features, response to treatment and immunological features which may distinguish LOMG from the early onset patients (who will also be recruited as controls). Who to refer? ▸ All patients should be over the age of 18 years, able to provide informed consent. ▸ The study aims to recruit patients who are willing to travel to one of the myasthenia clinics in Birmingham, Nottingham or Oxford ▸ All patients with a new diagnosis of MG (or diagnosed in the last 12 months) prior to immunosuppression. ▸ Diagnosis of MG based on typical clinical features and the presence of AChR or MuSK Abs, or evidence of neuromuscular transmission defect on single fibre EMG. What it involves for patients ▸ Management will be as per usual practice ▸ Annual serum samples at follow up with QoL and MG composite scores ▸ Follow up for 5 years (3 years by the clinical research fellow and 2 years optionally by the local participating neurologists).